If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18 + x = -2 Solving 18 + x = -2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-18' to each side of the equation. 18 + -18 + x = -2 + -18 Combine like terms: 18 + -18 = 0 0 + x = -2 + -18 x = -2 + -18 Combine like terms: -2 + -18 = -20 x = -20 Simplifying x = -20
| X^4+6x=0 | | 5x-7=103 | | (x^2-2)(x^2+3)=0 | | 170-5x=6x+5 | | 5x+1=3x+13 | | -4x^2-4x+3=0 | | 6p+3=3p+12 | | q=4.5-0.5 | | P^2-6p+8= | | 5x-2=x-14 | | 58-5=8+19 | | 2(x-12)=3(x-8) | | -9x^2=100 | | 6x^2+486=0 | | 15+3x=-3 | | y+2=5y+18 | | y=-0.125+1.375+1.5 | | 108-5x=31x+20 | | 6h+5=4h-17 | | 2w-2x-y+7w+15x-5y= | | 124-3x=6x+16 | | 11x-3y+13w+3y-4w+2x= | | 6w+9y+5x+8x-15y+4w= | | 2a+3(a-7)=a+3 | | 4(2x-5)=3(8-x) | | 4w+6x-13y+5w+7x+7y= | | 10n+7=107 | | 16a+17b+2c+2c-4b-3a= | | 2i+7=5i-2 | | 11p+19q+p-3q-6p= | | 3(2x-5)=27 | | x+(x+6)+12=66 |